LANTANIUM COMPOUNDS FLOTOEXTRACTION ISOLATION FROM DILUTE AQUEOUS SOLUTIONS - O. V. Perlova; V. F. Sazonova (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2014)
The high efficiency of the flotoextraction method for the lanthanum compounds removal from dilute aqueous solutions using the thin-emulsified higher carboxylic acids has been established. It is shown that the thin-emulsified decanoic and dodecanoic acids are the best collectors of the lanthanum compounds. The lantanium compounds can be removal using these acids by 90-97 % with a minimum flow of the collector consumption and high speed of the process. With the thin-emulsified heptanoic, octanoic and nonanoic acids the lanthanum compounds can be removaled by 85-93 % under the optimal conditions of the process.